Tai chi - Connor, Danny (Ebury Press, 1989)
Based on twenty years of tai-chi practice and observation, Danny Connor's thorough and wide-ranging text is a not-to-be-missed handbook for beginners and advanced follower alike on perhaps the most graceful and healing of all the martial arts.